2021
DOI: 10.1038/s41598-021-95290-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and environmental exposures and the breast cancer risk in Taiwanese women

Abstract: Breast cancer (BC) incidence is increasing around the globe, including in Taiwan, though the cause of the increasing incidence is less clear. We followed up 11,296 Taiwanese females who did not have BC at baseline, and ascertained new invasive BC (N = 351) through data linkage to the National Cancer Registry from 1991 to 2018 to examine whether reproductive, lifestyle and environmental risk factors including polycyclic aromatic hydrocarbons (PAH) were associated with BC risk. We conducted a nested case–control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2017, Shen et al found that plasma PHA was positively associated with breast cancer risk (39). However, Wu et al found no significant association between PHA and breast cancer in 2021 (40).…”
Section: Studies Not Eligible For Meta-analysismentioning
confidence: 99%
“…In 2017, Shen et al found that plasma PHA was positively associated with breast cancer risk (39). However, Wu et al found no significant association between PHA and breast cancer in 2021 (40).…”
Section: Studies Not Eligible For Meta-analysismentioning
confidence: 99%
“…Pain caused by widowhood or divorce and a range of unhealthy lifestyles are associated with the development of breast cancer (10,17). Also, lack of pregnancy and breastfeeding experience in unmarried women may be associated with breast cancer (18)(19)(20). Previous studies have shown that unmarried breast cancer patients are usually diagnosed at a late stage and have more depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The pain caused by widowhood or divorce and a series of following unhealthy lifestyles are associated with the onset of breast cancer (3,12). Meanwhile, the lack of experience of pregnancy and lactation in unmarried women may also be related to breast cancer (13)(14)(15)(16). Previous studies indicated that unmarried patients with breast cancer were usually diagnosed at an advanced stage and had more depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%